Percepciones de actores sociales de la cuenca Cumbaza (San Martín, Perú) sobre la Gestión Integrada de Recursos Hídricos - Gárate-Ríos, Jhonny (2025)
The aim of this study was to explore perceptions of Integrated Water Resources Management (IWRM) in the Cumbaza river basin, located in the Peruvian Amazon, by identifying key aspects for its effective implementation. To achieve this, interviews were conducted with key stakeholders and a reflexive thematic analysis was carried out, which led to the identification of seven perception areas related to IWRM. The discussion highlights the importance of inclusive water governance that engages diverse actors, improves the allocation of resources and infrastructure, and addresses critical environmental challenges. Furthermore, the study underscores the need to recognize community-led initiatives, raise awareness about IWRM, and develop policies tailored to the local context. The findings reveal an urgent need to strengthen water governance, protect aquatic ecosystems, and promote education and active participation in IWRM. In conclusion, the study offers valuable insights for the socially relevant implementation of IWRM in the Peruvian Amazon, providing guidance to enhance water management in the region.